Analysis of the Role of Internal And External Factors in Determining Students' Interest in Continuing Their Studies to Higher Education - Utomo, Eko Budi; Surjanti, Jun; Hakim, Luqman (Jurnal Pendidikan Edutama, 2025)
Study This aiming For analyze internal and external factors that influence interest student  For continue studies to college high . With use Systematic Literature Review (SLR) method , research This to study various relevant articles from 2015 to 2024. In the research This , SLR is important use reduce fragmentation through giving difference / relationship between One literature with others . Research samples is article from journal national and international . Research results show that interest student For continue education tall influenced by motivation personal , support family , environment school , and conditions social economy . Internal factors such as motivation and desire student play a role important in decision they , meanwhile factor external , including support from parents and information about choice education , is also very significant . Research This emphasize importance collaboration between schools , parents , and society in create supportive environment interest student For continue study . Findings This give outlook for educator and maker policy For designing an effective strategy in increase interest student For continue education to higher level tall .